Flame retardants: tris (2-butoxyethyl) phosphate, tris (2-ethylthexyl) phosphate and tetrakis (hydroxymethyl) phosphonium salts (Environmental health criteria)
El texto completo se encuentra disponible en la página: http://www.inchem.org/pages/ehc.html